2011
DOI: 10.3141/2207-07
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Moisture Loss and Strength Gain in Chip Seals

Abstract: One of the most subjective decisions made during chip seal construction concerns when to allow brooms and traffic on the newly placed surface. If traffic is allowed too early, damage to the surface and to vehicles may occur. If the chip seal is opened too late, traffic is disrupted and motorists are inconvenienced. The curing of asphalt emulsions in the field is related to many factors, all affecting how fast the asphalt emulsion cures. Three laboratory test methods that measure adhesive strength gain as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Yet, it is recognized that several researchers have questioned whether the sweep test can be reliably used as an indicator of chip seal performance ( 19 , 30 ). Nevertheless, based on the reviewed literature, the sweep test is still considered as one of the most popular test methods to investigate the aggregate loss performance of chip seals, given its low cost and the ease of the test procedure ( 17 , 18 , 31 ). In the current study, the sweep test was performed according to ASTM D7000 by replicating the sweeping action of a broom exerting force on the aggregate in the laboratory using a nylon brush.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Yet, it is recognized that several researchers have questioned whether the sweep test can be reliably used as an indicator of chip seal performance ( 19 , 30 ). Nevertheless, based on the reviewed literature, the sweep test is still considered as one of the most popular test methods to investigate the aggregate loss performance of chip seals, given its low cost and the ease of the test procedure ( 17 , 18 , 31 ). In the current study, the sweep test was performed according to ASTM D7000 by replicating the sweeping action of a broom exerting force on the aggregate in the laboratory using a nylon brush.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The chemical reactions between the aggregate As the water evaporates, the asphalt particles move closer together and begin to flocculate (James, 2006). At this early stage of the curing process, a considerable amount of water may have evaporated, but no appreciable mechanical strength has yet developed (Howard, Shuler, Jordan, Hemsley, & McGlumphy, 2011).…”
Section: Chip Seal Curing Process and Factors That Affect Curing Timementioning
confidence: 99%
“…Shuler and others Shuler, 2011) have reported a strong relationship between the moisture content and binder strength in a chip seal system. Howard et al (2011) measured chip seal binder adhesive strength gain as a function of moisture loss using three laboratory test methods: the sweep test (ASTM D7000, 2011), modified sweep test, and frosted marble test. Although all three tests are different, the results were similar and indicated that the strength in emulsion residue increases as the total moisture in the system is reduced, as shown in Figure 2.6.…”
Section: Current Approaches To Determine Chip Seal Curing Timesmentioning
confidence: 99%
See 2 more Smart Citations